How prepared are Canadian trauma centres for mass casualty incidents?. Issue 9 (September 2021) - Cameron, Andrew; Javidan, Arshia P; Nathens, Avery B; Cleghorn, Graham
Highlights: All Canadian Level 1 Trauma Centres were surveyed regarding their preparedness for a mass casualty incident (MCI), with a response rate of 46%. Most surveyed centres had adequate food, water, fuel, and communication assets for a hypothetical MCI. On average, responding trauma centre was able to mobilize a median 36 ward beds, 10 ICU beds, and 21 ED beds, and 38 ventilators. Areas for improvement include mandated training, collaboration with other organizations, and explicit Strategic Emergency Management Plans. Abstract: Objectives: Mass Casualty Incidents (MCIs) are rare but devastating events that require extensive planning in order to minimize morbidity and mortality. There are two broad categories limiting a hospital's response: physical assets (e.g., critical care beds, operating rooms, food, communication devices) as well as operating procedures (e.g., MCI committees, regional coordination, provider training). The purpose of this study is to provide an examination of MCI preparedness according to these categories in Level 1 Trauma Centre across Canada. Methods: This study surveyed all Level 1 Trauma Centres across Canada in order to assess the physical assets and operating procedures they had in place in the event of a hypothetical MCI on one of the busiest days of the year for trauma care. Results: Of the 28 Trauma Centres contacted, 13 completed surveys (46%). Most hospitals had sufficient food (9/13) water (9/13), fuel (7/13), and communication assets (8/13) for a hypothetical MCI. A median of 38 mechanical ventilators could be mobilized. No hospitals mandated physician training for MCIs, and 6/13 centres were certain that they had a Strategic Emergency Management Plan (SEMP). Only 6/13 hospitals had dedicated MCI committees, Overall, 4/13 hospitals had explicit plans developed with community hospitals. Conclusion: This study demonstrated that physical assets are generally less limiting than operating procedures. Four key areas of potential improvement have been identified: 1) provider training (especially physicians), 2) coordination with small hospitals, 3) mechanical ventilator availability, and 4) MCI committees with explicit Strategic Emergency Management Plans.